DYNAMIC VISUAL IDENTITY DESIGN FRAMEWORK FOR LOCAL MSME BASED ON BRAND VALUE AND BRAND ACTIVATION STEPS - Rahmadila Karimatun Nisa; Riky Azharyandi Siswanto; Wirania Swasty (ADISAM Publisher, 2026)
The rapid development of urban lifestyles in major cities in Indonesia has encouraged the emergence of various Micro, Small, and Medium Enterprises (MSMEs) from novice business players. This has led to many MSMEs experiencing differentiation challenges with competitors in the market. One of the challenges faced is the implementation of branding, including visual identity, which is not yet optimal, so that the brand value that is intended to be conveyed is not properly communicated to the audience. This study aims to develop a framework for designing a visual identity system for MSMEs that is dynamic and based on the brand value they wish to convey. This framework is developed based on academic and practical perspectives, with a synthesis of the results of a study of dynamic visual identity theory, observations of the workflow of practical branding designers, and categorization based on brand activation steps.